MODELING OF PLANT BIOMECHANICS AND MORPHODYNAMICS IN THE COMSOL PACKAGE - S. V. Nikolaev (Вавиловский журнал генетики и селекции)
This is a short review of the COMSOL Multiphysics package. Model building in COMSOL and methods of biophysical problem specification are demonstrated. Examples of the investigation of several problems in plant biomechanics and morphodynamics are considered.